The influence of volcanic ash (VA) on the mechanical properties and freeze-thaw durability of lime kiln dust (LKD)-stabilized kaolin clayey soil - Mohammad Hadi Hatefi; Mahyar Arabani; Meghdad Payan; Payam Zanganeh Ranjbar (Results in Engineering)
Improving soft clay soil's mechanical properties and durability has been the subject of intense research. In this context, traditional stabilizers such as cement and lime have been introduced as the most widely used materials. However, the utilization of these conventional additives poses several challenges due to recent global concerns regarding the reduction of greenhouse gas emissions. Therefore, international research is shifting toward using environmentally friendly soil-stabilizing waste materials. This study, for the first time, evaluates the stabilization of kaolin clay soil using lime kiln dust (LKD) as a high CaO content waste pozzolan and volcanic ash (VA) as a natural pozzolan with considerable SiO2 and Al2O3 contents. In general, the research aims to demonstrate the effective performance of these two inexpensive and environmentally friendly additives in improving the mechanical characteristics and durability of kaolin clay soil, thereby providing the essential groundwork for the practical application of this method in stabilizing soft clay soil. This study included preparing samples with LKD at 3%, 5%, 7%, and 10% of the dry weight of clay and replacing LKD with VA at 0%, 25%, 75%, and 100%. The specimens were cured for 3, 7, and 28 days. Following the curing process, the optimal sample was subjected to varying numbers of freeze-thaw (F-T) cycles. The samples were examined by conducting a series of standard compaction, unconfined compressive strength (UCS), ultrasonic pulse velocity (UPV), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) tests at different stages of adding stabilizers, as well as before and after exposure of F-T cycles. The findings revealed that adding LKD and VA increased the UCS by accelerating and improving the pozzolanic and hydration reactions. Also, the combination of LKD and VA in kaolin soil enhanced F-T durability, resulting in less strength deterioration even after 10 cycles, when compared to the untreated control sample. In particular, the optimal mixture containing 5% LKD and 25% VA replacement improved 11 times in UCS compared to untreated kaolin clay and showed a slight reduction of only 7% after 10 F-T cycles. Overall, the incorporation of LKD and VA enhanced the mechanical properties and F-T durability of kaolin clay soil, making it a low-cost, sustainable, and eco-friendly option for soil improvement.